Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy, 1989)
Commencing with Volume 21, the aim of this series is to produce a larger number of, relatively short but, timely and authoritative reviews. These will concentrate, in particular, on areas of NMR where recent progress, and developments, are of special interest and will reflect the many NMR developments occurring in the primary scientific literature. The present volume demonstrates the advances which can be made by the application of NMR techniques in many diverse areas of chemistry. Of particular significance is the account of Graphics-Aided NMR which will become an inprotant development in the use of NMR spectroscopy.